Representing masculinity : male citizenship in modern Western culture - Dudink, Stefan 1967- Herausgeber; Hagemann, Karen 1955- Herausgeber; Clark, Anna, 1957- 1957- Herausgeber (Studies in European culture and history, 2007)
"The idea that citizenship was the right of all humanity emerged during the French Revolution. However, this right was limited by gender, class and race. Studying Europe and its colonies and , the United States, Lebanon, and Dutch Indonesia, this book analyses images of masculine citizenship in political rhetoric, culture, art andand various colonial political struggles from the 18th to the 20th centuries. Politicians manipulated the rhetoric of masculine citizenship, using images of paternity and fraternity. Art represented competing images of the masculine citizen, ranging from the black revolutionary to the neo-Greek white statue. Colonial Political subjects in empires and colonies subjects appropriated and subverted these western ideals, revealing the exclusions in the rhetoric of masculine citizenship." -- Publisher's description.